The Relative Contribution of Executive Functions and Aging on Attentional Control During Road Crossing - Nicholls, Victoria I.; Wiener, Jan M.; Meso, Andrew Isaac; Miellet, Sebastien (Frontiers in Psychology, 2022)
As we age, many physical, perceptual and cognitive abilities decline, which can critically impact our day-to-day lives. However, the decline of many abilities is concurrent; thus, it is challenging to disentangle the relative contributions of different abilities in the performance deterioration in realistic tasks, such as road crossing, with age. Research into road crossing has shown that ageing and a decline in executive functioning (EFs) is associated with altered information sampling and less safe crossing decisions compared to younger adults. However, in these studies declines in age and EFs were confounded. Therefore, it is impossible to disentangle whether age-related declines in EFs impact on visual sampling and road-crossing performance, or whether visual exploration, and road-crossing performance, are impacted by ageing independently of a decline in EFs. In this study, we recruited older adults with maintained EFs to isolate the impacts of ageing independently of a decline EFs on road crossing abilities. We recorded eye movements of younger adults and older adults while they watched videos of road traffic and were asked to decide when they could cross the road. Overall, our results show that older adults with maintained EFs sample visual information and make similar road crossing decisions to younger adults. Our findings also reveal that both environmental constraints and EF abilities interact with ageing to influence how the road-crossing task is performed. Our findings suggest that older pedestrians’ safety, and independence in day-to-day life, can be improved through a limitation of scene complexity and a preservation of EF abilities.